Investigating the Effect of Malocclusion Severity on the Psychological Impact of Dental Aesthetics - Neda Babanouri; Hooman Zarif Najafi; Fatmeh Hosseini; Shabnam Ajami (Journal of Mashhad Dental School)
Background: Malocclusion can significantly influence psychological well-being, particularly concerning self-perception of dental aesthetics. The aim of this study was to evaluate the impact of malocclusion severity on the psychological impact of dental aesthetics in adult orthodontic patients.Methods and Materials: This cross-sectional study included a total of 255 healthy adults presenting to Shiraz Dental School and two private dental clinics in Shiraz, Iran. Participants were categorized into a case (undergoing fixed orthodontic therapy) and a control (without malocclusion) group.  Participants were asked to complete the Persian version of the Psychological Impact of Dental Aesthetics questionnaire (PIDAQ). This questionnaire comprises 23 items divided into four domains of Dental self-confidence, Social impact, Psychological impact and Aesthetic concerns. Malocclusion severity was assessed using the Dental Health Component of the Index of Orthodontic Treatment Need (IOTN). Additionally, the type of malocclusion (e.g., Class I, II, III, open bite, deep bite) and the type of orthodontic treatment (e.g., extraction, nonextraction, and surgery) were documented for case group participants. Spearman’s correlation coefficient and LSD-post hoc tests were used to analyze various associations. Statistical significance was established at P-value<0.05.Results: Participants undergoing fixed orthodontic therapy exhibited significantly higher overall PIDAQ scores and domain-specific scores compared to the control group (P<0.001 for all). There was a significant relationship between the the scores attained for the “Psychological impact” domain and IOTN scores (P=0.023). Subjects who required tooth extraction for orthodontic treatment exhibited significantly greater scores in the Aesthetic concern” domain, compared to nonextraction cases (P=0.031).Conclusion: PIDAQ scores were significantly greater in orthodontic patients compared to the control group. While the severity of malocclusion was not significantly associated with Dental self-confidence, Social impact, or Aesthetic concern scores, the type of orthodontic treatment influenced Aesthetic concern scores. These findings underscore the psychological benefits of orthodontic treatment.